Blood pressure regulation by endocannabinoids and their receptors - Pacher, Pál (2005)
Cannabinoids and their endogenous and synthetic analogs exert powerful hypotensive and cardiodepressor effects by complex mechanisms involving direct and indirect effects on myocardium and vasculature. On the one hand, endocannabinoids and cannabinoid receptors have been implicated in the hypotensive state associated with hemorrhagic, endotoxic and cardiogenic shock, and advanced liver cirrhosis. On the other hand, there is emerging evidence suggesting that the endocannabinergic system plays an important role in the cardiovascular regulation in hypertension. This review is aimed to discuss the in vivo hypotensive and cardiodepressant effects of cannabinoids mediated by cannabinoid and TRPV(1) receptors, and focuses on the novel therapeutical strategies offered by targeting the endocannabinoid system in the treatment of hypertension.